1992
DOI: 10.1557/jmr.1992.2798
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of orientation and graphitization of hard-carbon matrices in carbon/carbon composites

Abstract: It now appears generally accepted that the process of stress-induced orientation and graphitization of a thermoset-resin-derived matrix in a carbon-fiber/carbon-matrix (C/C) composite is principally a result of molecular orientation induced during the pyrolysis process as a consequence of the restraint of pyrolysis shrinkage at the fiber/matrix interface by attractive or frictional forces between fiber and matrix. We hypothesize that the critical factor for the formation of lamellar graphite (by subsequent hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 13 publications
3
10
0
Order By: Relevance
“…They detected enhanced ordering in graphite crystallinity by an increase of the 002 graphite reflection intensity. The mechanisms of orientation and graphitization of hard‐carbon was studied by Rellick et al (1992). They confirmed that during pyrolysis graphitization is a result of a molecular orientation process being enhanced by stress induced orientation of basic structural units.…”
Section: Introductionmentioning
confidence: 79%
“…They detected enhanced ordering in graphite crystallinity by an increase of the 002 graphite reflection intensity. The mechanisms of orientation and graphitization of hard‐carbon was studied by Rellick et al (1992). They confirmed that during pyrolysis graphitization is a result of a molecular orientation process being enhanced by stress induced orientation of basic structural units.…”
Section: Introductionmentioning
confidence: 79%
“…A further contribution to a partly recovery of the tensile strength during heat treatment above 1000 8C can expected to arise from the graphitisation of the matrix, although the matrix graphitises only locally [10]. During graphitisation of the matrix the basal planes orient parallel to the fibre direction.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…This orientation enables the activation of crack deflection mechanisms, which enhance composite strength. The local graphitisation of the matrix can be shown by transmission electron microscopy [4] or optical microscopy making use of polarised light [6,10]. A quantitative estimation of how much each of the involved phenomena contribute to the recovery of the strength is not possible as all phenomena take place simultaneously.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The measurement results varied significantly from sample to sample: 2 to 3 times from one pyrolysis loading and in different loadings. It is [8,9] contain information that not every carbonbase material is able to graphitize even at very high temperatures through the presence of nitrogen and oxygen bridges between disordered carbon clusters, which prevents from formation of extensive graphite structures. However, it was not proved for biomorphic carbon matrixes.…”
Section: Materials and Experimental Detailsmentioning
confidence: 99%